Faszyzm i nazizm w myśli Ludwiga von Misesa oraz Friedricha Augusta von Hayeka - Wojtyszyn, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
Ludwig von Mises and Friedrich August von Hayek, as representatives of created at the turn of the nineteenth century so-called Austrian School of Economics which promoted free-market solutions, and also as social-and-political thinkers, made socialism and totalitarian systems which derived from it one of the main points of their considerations. In their opinion, Fascism and National Socialism were a consequence of Marxian precepts, an adaptation of socialist solutions to local economic and political-and-legal conditions. Both economists drew attention to the fact that the program of centrally controlled economy and the German version of directed economy were impracticable due to the lack of efficiency in allocation of capital. Ludwig von Mises especially underscored the lack of pricing mechanism resulting from the nationalization of means of production which inevitably leads to the waste of wealth. He also emphasized that top-down management of economy requires introduction of limitations of individual liberty in other realms of life – private sphere, freedom of thought and speech, the way of spending leisure time. Friedrich August von Hayek concentrated on the impossibility of the full use of knowledge – which conditions progress and spontaneous development of society – in totalitarian systems. He stressed that the state founded on Marxian ideology or on fascist and Nazi descendants cousins of socialism is distinguished by its constant growth, incessant expansion of its tasks and the revocation of the rule of law which is replaced by the instrumental treatment of human beings in order to achieve desired social results. For both Mises and Hayek, in the above-mentioned totalitarian systems an individual becomes merely a tool in the hands of planners who try to impose their hierarchy of values and purposes on the rest of society.
Keywords: faszyzm; nazizm; Mises, Ludwig von (1881-1973); Hayek, Friedrich August von (1899-1992)